Genetic diagnosis of infantile‐onset epilepsy in the clinic: Application of whole‐exome sequencing following epilepsy gene panel testing. Issue 3 (3rd January 2021) - Kim, Soo Yeon; Jang, Se Song; Kim, Hunmin; Hwang, Hee; Choi, Ji Eun; Chae, Jong‐Hee; Kim, Ki Joong; Lim, Byung Chan
Abstract: This study aimed to evaluate the clinical utility of whole‐exome sequencing in a group of infantile‐onset epilepsy patients who tested negative for epilepsy using a gene panel test. Whole‐exome sequencing was performed on 59 patients who tested negative on customized epilepsy gene panel testing. We identified eight pathogenic or likely pathogenic sequence variants in eight different genes ( FARS2, YWHAG, KCNC1, DYRK1A, SMC1A, PIGA, OGT, and FGF12 ), one pathogenic structural variant (8.6 Mb‐sized deletion on chromosome X [140 994 419–149 630 805]), and three putative low‐frequency mosaic variants from three different genes ( GABBR2, MTOR, and CUX1 ). Subsequent whole‐exome sequencing revealed an additional 8% of diagnostic yield with genetic confirmation of epilepsy in 55.4% (62/112) of our cohort. Three genes ( YWHAG, KCNC1, and FGF12 ) were identified as epilepsy‐causing genes after the original gene panel was designed. The others were initially linked with mitochondrial encephalopathy or different neurodevelopmental disorders, although an epilepsy phenotype was listed as one of the clinical features. Application of whole‐exome sequencing following epilepsy gene panel testing provided 8% of additional diagnostic yield in an infantile‐onset epilepsy cohort. Whole‐exome sequencing could provide an opportunity to reanalyze newly recognized epilepsy‐linked genes without updating the gene panel design. Abstract :